Diseño de un sistema para el tratamiento de aguas residuales domiciliarias en el cantón mejía, provincia de Pichincha - Quishpe Hurtado, Sandra Belen (2020)
The main objective of this project is to select a household wastewater treatment for the homes of Canton Mejía, with emphasis on natural treatments of direct infiltration in the field with the design of a septic tank and two infiltration ditches, as a sustainable alternative and Low cost to reduce contamination of freshwater channels and enhance the use of waste water for irrigation. This research was developed through the collection of technical information from specialized agencies and international experiences. For the design, an initial flow of 600 / day per 4 inhabitants of each domicile was started, so the development of the calculations to determine the dimensions and volume of the septic tank and the infiltration trench taking into account the design criteria for each one of them. The design specifications for this project are defined as follows for septic tank design with hydraulic retention time Tr = 0.666 days, sludge sedimentation volume Vd = 10m ^ 3, sludge storage volume Vl = 0.4m ^ 3 cream volume 0.7m ^ 3, safety volume 0.10m ^ 3 The dimensions needed for the flow of 4 people are the width of 1.4m, a length of 2.8m, and the depth of 3 m. For the infiltration ditches, the length of 5.44 m is taken into account, so according to international experiences it is advisable to build 2 ditches for better treatment, the trench according to the WHO studied technical specifications for the design of ditches and wells Infiltration indicates that the width of the trench should be 0.30 to 0.90 m while the depth should not be less than 2 m, so these criteria are taken for the proposal of this design.